Fossilization and degradation of archaeal intact polar tetraether lipids in deeply buried marine sediments (Peru Margin) - Lengger, Sabine; Hopmans, E.; Sinninghe Damste, J.; Schouten, S. (Wiley-Blackwell Publishing Ltd., 2014)
Glycerol dibiphytanyl glycerol tetraether (GDGT) lipids are part of the cellular membranes of Thaumarchaeota, an archaeal phylum composed of aerobic ammonia oxidizers, and are used in the paleotemperature proxy TEX86. GDGTs in live cells possess polar head groups and are called intact polar lipids (IPL-GDGTs). Their transformation to core lipids (CL) by cleavage of the head group was assumed to proceed rapidly after cell death, but it has been suggested that some of these IPL-GDGTs can, just like the CL-GDGTs, be preserved over geological timescales. Here, we examined IPL-GDGTs in deeply buried (0.2–186 mbsf, ~2.5 Myr) sediments from the Peru Margin. Direct measurements of the most abundant IPL-GDGT, IPL-crenarchaeol, specific for Thaumarchaeota, revealed depth profiles, which differed per head group. Shallow sediments (<1 mbsf) contained IPL-crenarchaeol with both glycosidic and phosphate head groups, as also observed in thaumarchaeal enrichment cultures, marine suspended particulate matter and marine surface sediments. However, hexose, phosphohexose-crenarchaeol is not detected anymore below 6 mbsf (~7 kyr), suggesting a high lability.In contrast, IPL-crenarchaeol with glycosidic head groups is preserved over timescales of Myr. This agrees with previous analyses of deeply buried (>1 m) marine sediments, which only reported glycosidic and no phosphate-containing IPL-GDGTs. TEX86 values of CL-GDGTs did not markedly change with depth, and the TEX86 of IPL-derived GDGTs decreased only when the proportions of monohexose- to dihexose-GDGTs changed, likely due to the enhanced preservation of the monohexose GDGTs. Our results support the hypothesis that in situ GDGT production and differential IPL degradation in sediments is not substantially affecting TEX86 paleotemperature estimations based on CL–GDGTs and indicates that likely only a small amount of IPL-GDGTs present in deeply buried sediments is part of cell membranes of active archaea. The amount of archaeal biomass in the deep biosphere based on these IPLs may have been substantially overestimated.